Determinantes socioeconômicos da coabitaç\~ao familiar dos jovens e da formaç\~ao de novos domicílios no Brasil urbano - Maria da Piedade Morais; Paulo Augusto Rego (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– The objective of this article is to understand the main socioeconomic determinants of family cohabitation and new household formation by young adults in Brazilian urban areas. Methodologically, the study adapts the models of De Vos (1989) and Granado and Castillo (2002) to the Brazilian case, using microdata from Brazilian Institute of Geography and Statistics - IBGE 2009 National Household Survey - PNAD. The work also intends to verify to what extent the family cohabitation and new household formation are related to the conditions prevailing in the housing market, in order to subsidize the elaboration of housing policies more appropriate to the needs of the young population.
Keywords: R15; R21; R31; R38; C33; J32; J13; 330; cohabitation; new household formation; adulthood transition; leaving parental home; housing demand; housing policy; Brazil